1995
DOI: 10.1271/bbb.59.331
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cellulose fromD-Mannitol byAcetobacter xylinumKU-1

Abstract: We found that Acetohacter xylinum KU-l produced cellulose from D-mannitol. The optimum culture conditions for cellulose production were 1.5% D-mannitol, 0.5% Poly peptone, 2.0% yeast extract, pH 5, 30 o C, and 48 h. The amount of cellulose from D-mannitol was more than 3 times as much as that from D-glucose under the same culture conditions [productivity (mg/ml-medium): from D-mannitol, 4.6; from D-glucose, 1.2].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 3 publications
0
25
1
Order By: Relevance
“…Yeast extract and polypeptone are the most commonly used nitrogen source in BC production as it provides convenient nitrogens and growth factors for Acetobacter strains [6][7][8]. However, the high cost of yeast extract and polypeptone has a negative impact on the economics of its use in industrial-scale processes.…”
Section: Effect Of Molasses and Csl On Bc Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast extract and polypeptone are the most commonly used nitrogen source in BC production as it provides convenient nitrogens and growth factors for Acetobacter strains [6][7][8]. However, the high cost of yeast extract and polypeptone has a negative impact on the economics of its use in industrial-scale processes.…”
Section: Effect Of Molasses and Csl On Bc Productionmentioning
confidence: 99%
“…Therefore, one of the key aspects in the fermentation process is the development of a cost-effective culture medium to obtain maximum product yield. Most of the studies on the BC production by Acetobacter strains have been carried out in media containing pure sugar as carbon source, such as glucose, sucrose, fructose, mannitol, and arabitol [6][7][8]. The majority of studies on BC production have also used media containing complex nitrogen and vitamin sources such as yeast extract and polypeptone [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The optimum pH for cellulose production is 5.0 (13,16), and 3 production is associated with and proportional to growth (17). Cellulose production has been demonstrated from glucose, sucrose, fructose, glycerol, mannitol, arabitol, and many other substrates (5,13,16,18). Excess glucose is oxidized to gluconate in wild-type A. xylinum, which lowers the pH and inhibits cellulose production (13).…”
Section: Introductionmentioning
confidence: 99%
“…3, glycerol seems to be the best carbon source as a highest cell density (OD 600 ∼ 4.6) was obtained after 7 days cultivation. It has been reported that A. xylinum not only could metabolize mannitol but also a threefold higher growth could be obtained when compared with using glucose as carbon source [35]. However, as shown in Fig.…”
Section: Growth Curves Of Daao + a Xylinummentioning
confidence: 86%